2020
DOI: 10.21608/mb.2021.71824.1031
|View full text |Cite
|
Sign up to set email alerts
|

The human health problems of authorized agricultural pesticides: The Algerian case

Abstract: National authorized pesticides used in agriculture are one hot spot issue to human health especially for those working in the field. The aim of this study is to evaluate the health problems of authorized pesticides. Risk assessment was evaluated by 1) Toxicological classification of the WHO, and 2) Bio-Pesticides Database (BPDB) and Pesticide Properties Data Base (PPDB). The 2015 Algerian index of phytosanitary products used in agriculture includes 173 active ingredients (IAs) belonging to 83 chemical groups r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…17) The pesticides used in agriculture are a key issue in human health, especially for those working in the field. 18) Over the years, the prolonged use of chemical pesticides has made the common pistachio psylla resistant to many pesticides, while these pesticides have had a destructive effect on natural enemies. 19) Recent studies have shown the significant effect of using diatomaceous earth and inorganic fertilizers for pest control.…”
Section: Discussionmentioning
confidence: 99%
“…17) The pesticides used in agriculture are a key issue in human health, especially for those working in the field. 18) Over the years, the prolonged use of chemical pesticides has made the common pistachio psylla resistant to many pesticides, while these pesticides have had a destructive effect on natural enemies. 19) Recent studies have shown the significant effect of using diatomaceous earth and inorganic fertilizers for pest control.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of this insecticide in the environment could be unhealthy for bees, resulting in poor honey production. Also, the metalaxyl-M, a fungicide found in all samples, is the active ingredient used in several plant protection products on the Algerian market [45]. However, although the carbaryl is one of the 23 the substances banned from the Algerian market, residues of this pesticide were found in almost all samples.…”
Section: Pesticide Pcb and Pah Residuesmentioning
confidence: 96%
“…The presence of this insecticide in the environment could be unhealthy for bees, resulting in poor honey production. Also, metalaxyl-M, a fungicide found in all samples, is the active ingredient used in several plant protection products on the Algerian market [45]. However, although carbaryl is one of the 23 substances banned from the Algerian market, residues of this pesticide were found in almost all samples.…”
Section: Pesticides Pcbs and Pahsmentioning
confidence: 97%